Innovative textile structures designed to prevent type III endoleaks in endovascular stent‐grafts. Issue 3 (20th October 2020) - Lin, Jing; Nutley, Mark; Li, Chaojing; Douglas, Graeham; Du, Jia; Zhang, Ze; Douville, Yvan; Guidoin, Robert; Wang, Lu
Abstract: The damage caused to the fabric of endovascular stent‐grafts most often occurs at the contact zones between the fabrics where they are attached to the apices of Z‐shaped stents as a result of normal physiologic pulsatile movement within angulated vessels in vivo. Although design improvements were made over the years, the risks were not fully eliminated even with the newer M‐shaped stent reconfiguration. In this study, we proposed to create and manufacture a novel fabric for stent‐grafts with specifically designed reinforced zones to enhance resistance to fabric abrasion. These reinforced zones are set at the vicinity of the apices of the Z‐shaped stents and between two adjacent Z‐shaped stents where folding and pleating are commonly observed to occur in angulated vessels. Three innovative weaving structures with two different types of yarns and two controls were designed and prepared. Two commonly used commercial devices supported, respectively, with ringed stents, and Z‐shaped stents were selected as the references for comparison. Textile structures including thickness, water permeability, mechanical properties, (more specifically tensile and bursting stress, as well as fatigue simulation) were tested on all fabrics. Compared to commercially available plain weaves, the fabrics with locally reinforced zones showed improved mechanical characteristics and fatigue resistant properties. A fabric designed with specifically reinforced zones has now clearly been shown to effectively reduce the abrasion caused by the apices of Z‐shaped stents. However, further optimization may still be possible. Abstract : A novel fabric for stent‐grafts with specifically designed reinforced zones to enhance resistance to a fabric abrasion.